(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول البحث دراسة تأثيرات الارتفاع في أسعار النفط على الاقتصاد السوري , ففي البداية يتم دراسة تطور أسعار النفط في الفترة 2000 – 2005 ومن ثم الخوض في الأسباب التي أدت إلى الارتفاع الكبير في الأسعار سواء المتعلقة منها بالظروف السياسية التي رافقت الفترة المدروسة أو العوامل المتعلقة بازدياد الطلب على النفط .... ومن ثم يحاول البحث الفصل بين تلك العوامل اعتماداً على معيار ديمومتها في محاولة للتنبؤ بمستقبل أسعار النفط في الفترة القادمة وفي النهاية يحاول البحث تقديم عدة مقترحات لمواجهة تأثيرات تغير أسعار النفط صعوداً حيث يركز البحث على محورين أساسيين المحور الأول متعلق بتخفيض النفقات الحكومية, والمحور الثاني يركز على خلق موارد حكومية جديدة .ويخلص البحث إلى اقتراح استراتيجية وطنية لمواجهة التأثيرات السلبية لتغيرات أسعار النفط على الاقتصاد الوطني. The study examines the effects and implications of the increase of petroleum prices on Syrian economy. First, the study deals with the development of petroleum prices in the period of 2000 to 2005. Then, it goes deep in the reasons that led to the huge rise of prices either relating to the political circumstances in this period or the factors relating to the increase of demand on petroleum Meanwhile, it separates between such factors based on their continuity and the anticipation of future petroleum prices. Finally the study offers several proposals to face the effects of fluctuating petroleum prices as uprising the study focuses on the two main factors: 1. The first factor is related to reducing the government charges. 2. The second factor is related to create new government resources. Finally the study suggests national strategy to face the negative influences of the increase of the petroleum prices on the national economic.